2012
DOI: 10.1111/j.1744-7410.2011.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of energy metabolism and resistance to dehydration in the invasive slug Limax maximus

Abstract: Abstract. Standard metabolic rate (SMR) and resistance to body dehydration (BD) are important physiological traits that have an effect on water balance and the amount of energy available for activity and production, and thus could contribute to variation in life history traits expressed across a range of environments. Few studies have tested whether SMR and BD show consistent between-individual variation in molluscs. Significant repeatability of SMR and BD indicates that the traits might be heritable and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…In this study, standard metabolic rate (SMR), the obligatory maintenance energy cost in ectotherms [52], was measured as the rate of carbon dioxide production using an open system, as described by Gaitán-Espitia et al (2012) [53]. Briefly, CO 2 production at 20°C was measured continuously with an infrared CO 2 analyzer (LI-COR 7000 Sable System®) capable of resolving differences of up to 1 part per million of CO 2 in air, connected to a computerized data-acquisition system (Expe Data software, Sable Systems), similar to one used by [54].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, standard metabolic rate (SMR), the obligatory maintenance energy cost in ectotherms [52], was measured as the rate of carbon dioxide production using an open system, as described by Gaitán-Espitia et al (2012) [53]. Briefly, CO 2 production at 20°C was measured continuously with an infrared CO 2 analyzer (LI-COR 7000 Sable System®) capable of resolving differences of up to 1 part per million of CO 2 in air, connected to a computerized data-acquisition system (Expe Data software, Sable Systems), similar to one used by [54].…”
Section: Methodsmentioning
confidence: 99%
“…Terrestrial mollusks face two important challenges, dehydration and the energetic costs of locomotion (Denny 1980;Rizzatti and Romero 2001;Czarnołęski et al 2008;Gaitán-Espitia et al 2012). Previous studies of C. aspersum in Chile have shown that physiological traits at the whole-animal level are remarkably constant and repeatable across the geographical range (Artacho and Nespolo 2008;Naya et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…To avoid any noise or erroneous recordings generated by animal manipulation, we eliminated the first 10 min of the record (600 samples) (Gaitán-Espitia et al, 2012). From each individual record, we extracted the average of each transformed record (V · CO2,mean ) which is used here as a proxy of SMR.…”
Section: Energy Expenditure and Water Balancementioning
confidence: 99%
“…body dehydration), the snails were weighed at the beginning of each trial, when the animals were fully hydrated, and at the end of the test period (i.e. 45 min), recording the mean M b and also the differences between initial and final M b as a proxy for body water loss (Gaitán-Espitia et al, 2012).…”
Section: Energy Expenditure and Water Balancementioning
confidence: 99%
See 1 more Smart Citation